Finding Damage Localizations of a Planar Truss Using Modal Strain Energy Change - Xiaoshun Wu; Juwei Xia; Xuekun Zhu (Advances in Civil Engineering)
A novel structural damage localization method based on modal strain energy changes is proposed. The proposed method does not utilize the first several modes together as usual but selectively makes use of some sensitive modes for each element. Both the magnitude of normalized elemental modal strain energy and the capability of each element to resist identification uncertainties are considered to determine the sensitive modes. Elements’ capability to resist identification uncertainties is calculated by using the Monte Carlo method. Based on determined sensitive modes, an in-turn damage-checking process is employed to judge the damage state of each element. A typical planar truss is numerically analyzed. The results show that the proposed method is more effective than that based on modal strain energy change ratio even when using the first several modes together as usual. Furthermore, by utilizing some sensitive modes only, the proposed method becomes much more robust, making damage localization more easy and reliable.